Pandangan Pengarang terhadap Perempuan dalam Cerpen Tahun 1950-1960-an Karya Pengarang Peranakan Tionghoa-Indonesia - Dwi Susanto (Universitas Mulawarman, 2022)
This paper looks at the views or constructions of Chinese peranakan authors towards women in that era. Issues discussed: (1) how Peranakan authors narrate women in their works; (2) the reasons for the Chinese Peranakan authors in the 1950s-1960s to narrate women. This study uses the point of view of feminist literary criticism. The object of this research is the 1950-1960s short stories and the author's perspective on women. The data of this research is the narrative of short stories that describe the image of women, the author's social construction, and the idea of ​​androcentrism. The data interpretation technique follows the way of feminist literary criticism. The results of the study: (1) women are presented and controlled by men and are controlled by social construction; (2) the idea of ​​morality and the economic context becomes a construction that the author interprets through androcentrism; (3) morality is misinterpreted by male authors and women as victims who are silenced in the name of morality. It has resulted in women being unable to speak up and follow androcentrism in the name of tradition and the sacred concept of morality. Morality is misinterpreted as sexuality and borne by women.